Bisnis Tanam Bulu Mata Perspektif Ekonomi Islam (Studi Kasus Salon Dena Beauty) - Munir, Ridwan; Isnayani, Inta (STAI Al Musaddadiyah Garut, 2023)
Eyelash Extension is a type of female treatment in the form of planting strands of false eyelashes on the eyelids so that the eyelashes look thicker and curlier, but this is against islamic law. The formulation of the problems in this research are 1. How is the eyelash extension business at Dena Beauty salon? 2. How is the eyelash extension business in the perspective of islamic economic law? From the formulation of the problem, the target of this research is to 1. Know the eyelash extension business at Dena Beauty Salon. 2. To find out the legal perspective of islamic economics towards the eyelash extension business This research is included in the type of field research which is qualitative descriptive in nature, namely a method that describes the situation that occurs in the field systematically. In the required data, the authors used preliminary research and interviews according to the issues discussed. Bassed on the results of the study it can be included that the eyelash growing business in the perspective of islamic economic law is haram because it uses objects that are prohibited by islam.